Uniportal video-assisted thoracoscopic right upper lobectomy with systematic lymphadenectomy - Shen, Gang; Chai, Ying; Huang, Lijian; Yang, Maoying; Zhang, Guofei (Journal of Thoracic Disease, 2016)
Over the past decade, uniportal video-assisted thoracic surgery (VATS) has been reported to be a promising, less invasive alternative with potentially better cosmesis and less postoperative pain and paraesthesia. Although uniportal VATS has now evolved into a sophisticated technique capable of performing some of the most complex thoracic procedures, this approach to lobectomy is not standardized, and the surgical procedure still varies between surgeons. Here, we describe our uniportal VATS procedure during right upper lobectomy in a patient with a nodule in the right upper lobe. Subsequent mediastinal lymphadenectomy was performed to remove lymph nodes from the 2nd, 3rd, 4th, 7th, 8th, and 9th groups. Although there are some details that are different compared to the conventional VATS approach, as experience with uniportal VATS has grown, this approach is a viable alternative approach for lobectomy in selected patients.